Development and kinematic analysis of crank slider mechanism (with crank wheel) / Aidil Ashraf Mohd Adnan - Mohd Adnan, Aidil Ashraf (2022)
Crank Slider Mechanisms is mechanical mechanisms that convert rotational motion to linear motion and vice versa Applications are widely used in most mechanical machines The aim of this study is to design and fabricate a well-functioning Crank Slider Mechanism A relative motion analysis (kinematic analysis) will be conducted to design a well-functioning mechanism. Then, the procedure of this study will be extended to experimental use once the fabrication of the mechanism is completed. As a conclusion of this study, a comparison between experimental data and calculation data will be conducted and discussed